A Cone – Beam Computed Tomographic Assessment of The Prevalance and Inter-orifice Distance of Second Mesiobuccal Canal Present in Maxillary First Molars in Lucknow Population – A Retrospective Study - Dr. Tanu Tewari, Dr. Vishesh Gupta, Dr. Ria Saigal, Dr. Gunja Verma (Journal of Daoist Studies, 2026)
Aim and objectives: Using CBCT, ascertain MB2’s incidence and inter-orifice distance of MB1-MB2 and MB2-PC in maxillary first molars in a specific Lucknow population using CBCT technique. Methodology: One hundred CBCT scans of maxillary first molars meeting inclusion criteria were retrospectively analyzed. The presence or absence of the MB2 canal was recorded. For teeth with an MB2, the linear distances between the centres of the MB2 and MB1 orifices and between the MB2 and PC orifices were measured at the pulpal floor level using specialised 3D imaging software. Data were analyzed using descriptive statistics and chi-square tests. Results: The MB2 canal was present in 68% of the studied maxillary first molars. The mean inter-orifice distance between MB1 and MB2 was 2.03 ± 0.50 mm, ranging from 0.70 mm to 3.80 mm. The mean distance between MB2 and the Palatal Canal was 4.92 ± 0.92 mm, ranging from 3.3 mm to 6.5 mm. The high prevalence confirms the MB2 as a common anatomical feature in this population. Conclusion: The MB2 canal is highly prevalent in the maxillary first molars of the Lucknow population. The measured inter-orifice distances provide clinically valuable, population-specific guidelines for access cavity modification and targeted troughing, promoting a proactive "search and treat" approach to improve detection rates and the long-term success of endodontic therapy.